Icaritin‐induced immunomodulatory efficacy in advanced hepatitis B virus‐related hepatocellular carcinoma: Immunodynamic biomarkers and overall survival. Issue 11 (24th September 2020) - Qin, Shu‐Kui; Li, Qing; Ming Xu, Jian; Liang, Jun; Cheng, Ying; Fan, Ying; Jiang, Jun; Ye, Hao; Tao, Huimin; Li, Lian; Zheng, Limin; Wei, Zhaohui; et al.
Abstract: Advanced hepatitis B virus (HBV)‐related hepatocellular carcinoma HCC with poor prognosis is often associated with chronic inflammation, immune tolerance, and marked heterogeneity. The interleukin‐6 (IL‐6)/JAK/STAT3 signal pathways play multiple regulatory roles in modulating inflammation and immunity in cancers. Polarization of myeloid‐derived suppressor cells (MDSCs) is involved in HBV‐related immunosuppression and CD8 + T‐cell activation through ERK/IL‐6/STAT3. Icaritin is a small molecule that has displayed anticancer activities through IL‐6/JAK/STAT3 pathways in tumor cells and immune cells including CD8 + T cells, MDSCs, neutrophils, and macrophages. This study aimed to confirm icaritin immunomodulation in advanced HBV‐related HCC patients with poor prognosis. Immunomodulation of MDSCs was evaluated in BALB/c mice in vivo. Immunomodulation of serum cytokines and a panel of immune checkpoint proteins were assessed in HBV‐related, histologically confirmed HCC patients. Poor prognostic characteristics included HBV infection, bulky tumors, Child‐Pugh B classification, and metastasis. Clinical end‐points included safety, tumor response, and overall survival (OS). Icaritin treatment‐induced dynamics of serum cytokines IL‐6, IL‐8, IL‐10, and tumor necrosis factor‐α, and soluble immune checkpoint proteins TIM3, LAG3, CD28, CD80, and CTLA‐4 were assessed. No grade III/IV treatment‐related adverse events were observed. Time‐to‐progression was significantly associated with the prognostic factors. Improved survival was observed in the advanced HCC patients with dynamic changes of cytokines, immune checkpoint proteins, and immune cells. Median OS (329‐565 days) was significantly correlated with baseline hepatitis B surface antigen positivity, cytokines, tumor neoantigens, and Stenotrophomonas maltophilia infection. Composite biomarker scores of high‐level α‐fetoprotein and T helper type I (Th1)/Th2 cytokines associated with favorable survival warrant further clinical development of icaritin as an alternative immune‐modulatory regimen to treat advanced HCC patients with poor prognosis. Abstract : Advanced hepatitis B virus (HBV)‐related hepatocellular carcinoma (HCC) is often associated with chronic inflammation, liver injury, immune tolerance, and poor clinical outcomes. Due to drug toxicity and side‐effects, current targeted drugs including sorafenib are unfortunately not favorable treatment options, particularly for those advanced HCC patients with poor prognosis. Herbal‐derived natural small molecule icaritin showed anticancer immunomodulatory efficacy with superior safety and improved survival associated with coordinated immune dynamics. Composite biomarkers associated with favorable survival would warrant further clinical development of icaritin as an alternative "natural compound" immune therapy in advanced HBV‐related HCC patients with poor prognosis.